MEDIATIZATION: ENCOURAGING THE EXISTENCE OF SUBCULTURES THROUGH THE MEDIA - Yudha, Reza Praditya (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2023)
This article discusses Citayam Fashion Weeks from a mediatization perspective. The purpose of this article is to examine the socio-cultural dynamics behind the Citayam Fashion Weeks phenomenon. This article argues that the ease of using the media has encouraged the birth of subcultures into the public sphere. The findings of the study show that the media make it easier for subcultures to gain existence. The logic of the media then creates a shift in meaning and banalization of the identity of Citayam Fashion Weeks as a subculture. The existence of subcultures is then related to their ability to adapt to large figurations in the surrounding environment.